2007
DOI: 10.1158/0008-5472.can-07-0666
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-W Is a Novel Marker for Activated Tumor Stroma in Low-grade Human Breast Cancer and Influences Cell Behavior

Abstract: This is the first report about human tenascin-W, the fourth and final member of the extracellular matrix protein family of tenascins. Sixty-three human breast tumor extracts were analyzed by Western blotting for the presence of tenascin-W and compared with tenascin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 52 publications
6
73
0
Order By: Relevance
“…A similar correlation has been found for tenascin-W in mouse models of mammary cancer, where stromal tenascin-W expression was particularly prominent in those cancers known to metastasize (Scherberich et al 2005). So far such a correlation was not observed in human breast cancer where tenascin-W expression was higher in low-grade than in high-grade cancers (Degen et al 2007). However, in colon cancer tenascin-W may correlate with the severity of the disease because serum levels of patients with nonmetastatic colon cancers were higher in those patients that suffered a recurrence ).…”
Section: Tenascins In Cell Migration Cancer Cell Invasion and Metassupporting
confidence: 72%
See 1 more Smart Citation
“…A similar correlation has been found for tenascin-W in mouse models of mammary cancer, where stromal tenascin-W expression was particularly prominent in those cancers known to metastasize (Scherberich et al 2005). So far such a correlation was not observed in human breast cancer where tenascin-W expression was higher in low-grade than in high-grade cancers (Degen et al 2007). However, in colon cancer tenascin-W may correlate with the severity of the disease because serum levels of patients with nonmetastatic colon cancers were higher in those patients that suffered a recurrence ).…”
Section: Tenascins In Cell Migration Cancer Cell Invasion and Metassupporting
confidence: 72%
“…Osteosarcoma and bladder carcinoma cells adhere to a tenascin-X substratum, but they did not spread or assemble stress fibers (Elefteriou et al 1999) and p38 MAPK was identified as the major mediator of tenascin-X-induced cell detachment of mouse L cells (Fujie et al 2009). Addition of tenascin-W to the culture medium of cancer cells (Scherberich et al 2005;Degen et al 2007) as well as primary osteoblasts (Meloty-Kapella et al 2006;Meloty-Kapella et al 2008) stimulated their migration toward a fibronectin substratum in vitro. Thus, a common activity of all tenascins seems to be their ability to modulate cell adhesion and migration.…”
Section: Tenascins and The Importance Of Adhesion Modulationmentioning
confidence: 99%
“…In vitro, tenascin-W causes dramatic changes in the shape of osteoblasts (Meloty-Kapella et al 2006), C2C12 cells (Scherberich et al 2004), and Detroit 551 fibroblasts (Degen et al 2007). In each case, cells cultured on tenascin-W are rounded, bipolar, or stellate with phalloidin-stained ruffles at the tips of processes.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2). In most carcinoma cases, it is produced and localized in the tumor stroma, but the cancer cells themselves are mostly devoid of TNC (3,4). This is, however, different in glioblastoma (GBM) where the highly invasive cancer cells are the source of TNC themselves.…”
Section: Introductionmentioning
confidence: 99%